Development of electricity generating system for a micro-power plant - Kareem, Buliaminu; Ewetumo, T.; Adeyeri, M. K.; Oyetunji, A.; Olowookere, S. T. (Journal of Production Engineering, 2018)
The move from fossil fuel to clean energy has become the focus of the 21st century, to suplement the energy needs of the world which have been on the increase. This research tackles the challenge of energy inadequacy by designing and fabricating electric generator for micro-power plant using locally sourced materials. The design of the 5.5kW induction generator involved the application of recycling technique on the discarded scrap motor. Discarded electric motor after cleaning was redesigned and rewound to give an electric power output of 5.5 kW. The generator was tested under load and no load conditions. The outcomes showed that the generator can adequately carry a load of 2.3 kW when operated at speed ranging between 2300 and 2400 pm. The output voltage ranging between 150 V and 190 V, while the ouput current was in the range 6.07A and 6.35A. Higher load carrying capacity, 5.0 kW was achievable at the rotory design speed, 3000 rpm with the maximum voltage and current limits, 239.6 V and 10.467 A, respectively. The 3-phase induction generator was able to sustain higher power output, 5.0 kW of the design capacity.